Is maturational growth more influential than training engagement in longitudinal adolescent physical performance development? - Abbott, S.; Javet, M.; Bested, S.; Hackett, D.; Romann, M.; Cobley, S. (European Journal of Sport Science, 2025)
Athlete development is considered a multi-factorial and dynamic overtime process. Thus, understanding what factors and behavioural activities contribute most to development is important. The present study examined longitudinal relationships between training time and maturity status with physical performance indices in youth volleyball players. Prospective mixed longitudinal tracking over 3 years. Participants were N = 78 selected male volleyball players, aged 11-15 years (M = 13.81, SD = 1.20 years) from N = 41 competitive Swiss clubs. Alongside coach-reported weekly training time, participants completed standardised anthropometric and physical performance tests (e.g., standing long jump [SLJ]; 9-3-6-3-9 agility sprint). Linear mixed models (LMM) examined longitudinal independent and interacting relationships between training time and maturity status (years from peak height velocity; PHV) with physical performance. For SLJ, both training time and maturity status explained curvilinear longitudinal performance development, but nonlinear maturation status interactions were most influential, moderating relationships. In agility sprint, similar trends were apparent, with training time influences diminishing when maturity status was added in LMM analyses. Across time points of maturational growth, increased training engagement was not associated with enhanced physical performance benefits, whereas maturational status progression better accounted for performance differences and development. For coaches and sports-science practitioners, findings question the rationale for heightened training engagement at circa-PHV directed towards physical performance development purposes, a recommendation aligned with the need for maturational-growth associated injury prevention. Instead, due to musculoskeletal and proprioceptive disturbance during maturational growth, training emphasis on technical/biomechanical skill acquisition remains important.